Peranan Orang Tua dalam Mengajarkan Anak Usia Dini Membaca - Dyla Fajhriani N; Afnibar Afnibar; Nurul Jariah; Yulia Novita Sari; Ria Hayati (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2023)
As parents, teaching children to read needs to practice patience, especially at the PAUD level. Learning activities carried out in PAUD parks focus more on playing activities compared to reading. Teaching children to read requires patience because teaching reading not only makes children able to read but also fosters interest in reading until children grow up. When parents teach children to read, it needs to be done through activities that are liked by children such as giving color to the words to be read to children, even teaching reading will encourage children to continue learning. The research method used namely library research. This article aims to explain the role of parents in teaching children to read at an early age.